A CRITICAL ANALYSIS OF THE IMPORTANCE OF RELIGIOUS INSTITUTION ACCOUNTABILITY FROM THE PERSPECTIVE OF PEMEDEK: BETWEEN SPIRITUALITY AND TRANSPARENCY - I Gusti Agung Prama Yoga; Desak Rurik Pradnya Paramitha Nida; Ida I dewa Mas Manik Sastri (RADJA PUBLIKA, 2026)
Accountability in religious organisations is commonly interpreted through financial reporting and governance mechanisms, overlooking the influence of indigenous cultural and spiritual values. This study explores how accountability is socially constructed from the perspective of worshippers (pemedek) at Pura Agung Besakih, Bali. Employing a qualitative ethnographic approach and Bourdieu's Theory of Practice, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that accountability extends beyond administrative transparency and is rooted in the religious values of dharma, bhakti, and yadnya, which cultivate religious habitus and spiritual trust. These values are institutionalised through Purana and awig-awig, generating symbolic capital that legitimises temple governance. Accountability is further reinforced by the principles of karmaphala and the relationship between sekala and niskala, functioning as internal spiritual control mechanisms that encourage ethical behaviour. Administrative accountability complements, rather than replaces, this moral foundation by strengthening public trust through transparent financial management. Based on these findings, this study proposes an Inculturated Accountability Model, demonstrating that accountability in religious organisations is a culturally embedded process integrating religious values, customary institutions, symbolic legitimacy, spiritual control, and administrative transparency to support sustainable temple governance.